Techno-Economic Analysis and Optimization of Grid-Connected Hybrid Renewable Energy Systems Using Homer Pro - Khettab Zakarya; Alla Abdelaziz; OUBBATI Youcef (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electrotechnique, 2024)
This work discusses the techno-economic analysis of a hybrid renewable energy system using HOMER Pro. We used this tool to optimize and find the optimal conditions and configurations that could achieve economic efficiency for renewable energy investors. First, several scenarios of buying and selling prices to and from the grid were tested. We observed that the subsidized kilowatthour price by the government (in petroleum countries) affects the returns of renewable energy investors. On the other hand, the unsubsidized kilowatt-hour price encourages renewable energy investors with higher and better returns. Furthermore, with fixed buying/selling prices, various renewable energy scenarios and configurations were evaluated. The optimal system for maximizing economic efficiency and profitability is the hybridization of wind and solar energy, coupled with a reliable grid connection. This hybrid approach reduces carbon emissions and promotes environmental sustainability.
Electrical Power System